Ocena wykorzystania rachunków kosztów stosowanych w przedsiębiorstwach województwa warmińsko-mazurskiego - Dynowska, Joanna (The Evaluation of the Use of Modern Cost Accounting System in Companies Based in Warmińsko-Mazurskie Voivodeship, 2006)
According to the survey concerning the cost accounting systems, which was carried out among 169 firms with the employment over 50 workers, most of the analyzed firms still use only traditional cost accounting. This can cause a risk for leading companies to invest in the wrong assets and to allocate resources in the wrong products. It can also lead to making wrong decisions in income planning, optimal production plan, pricing policy, and whether or not to insource/outsource elements of the supply chain. Moreover, lack of experience in cost accounting results in defaulting mainly to absorption costing. Only a small precent of the companies implemented modern cost accounting techniques such as activity-based costing or target costing.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1139, s. 68-76